Persistently activated, proliferative memory autoreactive B cells promote inflammation in rheumatoid arthritis - Kristyanto, Hendy (Sci Transl Med, 2020)
Autoreactive B cells mediate autoimmune pathology, but exactly how remains unknown. A hallmark of rheumatoid arthritis (RA), a common autoimmune disease, is the presence of disease-specific anticitrullinated protein antibodies (ACPAs). Here, we showed that ACPA-positive B cells in patients with RA strongly expressed T cell–stimulating ligands, produced abundant proinflammatory cytokines, and were proliferative while escaping inhibitory signals. This activated state was found at different degrees in different stages of disease: highest in patients with recent-onset RA, moderate in patients with established RA, and far less pronounced in ACPA-positive individuals “at risk” for developing disease. The activated autoreactive B cell response persisted in patients who achieved clinical remission with conventional treatment. ACPA-positive B cells in blood and synovial fluid secreted increased amounts of the chemoattractant interleukin-8, which attracted neutrophils, the most abundant immune cell in arthritic joints. Tetanus toxoid–specific B cells from the same patients exhibited properties of memory B cells without the activation and proliferation phenotype, but these cells transiently acquired a similar proliferative phenotype upon booster vaccination. Together, these data indicated that continuous antigenic triggering of autoreactive B cells occurs in human autoimmune disease and support the emerging concept of immunological activity that persists under treatment even in clinical remission, which may revise our current concept of treatment targets for future therapeutic interventions. In addition, our data pointed to a pathogenic role of ACPA-positive B cells in the inflammatory disease process underlying RA and favor approaches that aim at their antigen-specific inactivation or depletion.